The 2007 Caribbean Community Port-of-Spain Declaration on noncommunicable diseases: an overview of a multidisciplinary evaluation - T. Alafia Samuels; Nigel Unwin (Pan American Health Organization, 2018)
Objectives. Noncommunicable diseases (NCDs) are a threat to social and economic development, including in the Caribbean. In 2007 the Caribbean Community (CARICOM) held the world's first-ever summit of heads of government on NCD prevention and control and issued the landmark Declaration of Port-of-Spain: Uniting to Stop the Epidemic of Chronic NCDs. The objectives of this paper are to provide an overview of a formal evaluation of the Declaration and to highlight key findings that could inform further implementation of the Declaration's 15 mandates. Methods. The evaluation's six research objectives were decided through stakeholder engagement and assessed by concurrent quantitative and qualitative research methods, using the following four themes: 1) trends in risk factors, morbidity, and mortality; 2) national and Caribbean-wide policy responses, and factors associated with policy successes and difficulties; 3) the international impact of the Declaration; and 4) the potential for raising revenue from tobacco and alcohol taxation in order to support NCD prevention and control. Results. There are marked disparities in NCD mortality and trends among the 20 CARICOM member countries and territories. No CARICOM member had fully implemented all of the Declaration's 15 mandates (which were monitored by 26 indicators), with 10 CARICOM members implementing fewer than half of the indicators, and with most members lacking a well-functioning multisectoral NCD Commission. Larger CARICOM members tended to have higher levels of implementation than did smaller members. Mandates that received active support from regional institutions tended to be better implemented by the CARICOM members than did mandates that lacked that kind of support. Feasible national tobacco and alcohol tax increases could more than cover the cost of implementing the World Health Organization NCD "best buy" interventions in the CARICOM member countries and territories. Conclusions. Priorities for further implementation of the mandates from the Port-of-Spain Declaration include establishing throughout the CARICOM member countries and territories fully functioning national bodies to support multisectoral action for NCD prevention; greater regional support in policy development and implementation for smaller countries; and greater targeted use of taxes on tobacco and alcohol to support NCD control and prevention.